Funding and Academic Performance of Secondary School Students in Oyo East Local Government Area of Oyo State - OLALEKAN, Abiodun Olawumi (International Journal of Educational Management, 2025)
The study investigates the influence of school funding on the academic performance of secondary school students in Oyo East Local Government Area of Oyo State. Descriptive survey design was adopted for this study. Simple random sampling was used to select 100 teachers from five public secondary schools in Oyo East Local Government Area of Oyo State. A questionnaire was used as an instrument for data collection. Three research questions and one hypothesis guided the study. Data collected were analyzed using simple percentages, computed mean scores and chi-square statistics. The findings revealed that there is a significant influence of funding on the academic performance of the students in public secondary schools. The calculated chi-square value derived from the study was (XCal =30.91). Based on the findings, it was recommended that there is a supportive atmosphere for teaching and learning, the government should put adequate accountability measures in order to ensure that the available funds are judiciously utilized in the schools. Teachers need to be given periodic training to update their k nowledge to ensure that what they are teaching the students are of good quality. Also, the P. TA. and other stakeholders should be more committed to fonding secondary education.